(untitled) (IAHS Medical Journal, 2024)
Background: Non-Communicable Diseases (NCDs) pose a significant health challenge globally, particularly in countries underwent rapid demographic transitions like Bangladesh. Rural populations, including postmenopausal women, are disproportionately affected by NCDs due to various socio-economic and lifestyle factors. This study aimed to investigate the prevalence of NCD risk factors among postmenopausal women in a rural village. This cross-sectional study was conducted in a rural village of Gazipur, Bangladesh from November 2023 to February 2024. Materials and methods: A sample of 108 postmenopausal women was selected using a convenience sampling technique. Data on socio-demographic characteristics, lifestyle habits and health outcomes were collected through structured interviews and assessments. Chi-square tests were employed to analyze the associations between sociodemographic variables, lifestyle factors and the presence of NCDs. Results: The study revealed a high prevalence of NCD risk factors among postmenopausal rural women. Engaging in physical activity for 2-4 hours daily was significantly associated with both Diabetes Mellitus (p 0.04) and Hypertension (p 0.006). Similarly, occupation showed a significant association with Hypertension (p 0.012) with housewives exhibiting higher prevalence rates. However, there were no significant associations between salt intake, sweet consumption and the presence of NCDs. Conclusion: This study highlights the urgent need for targeted interventions to address NCD risk factors among postmenopausal rural women in Bangladesh. Strategies focusing on promoting physical activity and addressing occupational factors could help mitigate the burden of NCDs in this vulnerable population. By understanding the socio-demographic and lifestyle determinants of NCDs, policymakers and healthcare providers can develop effective public health interventions tailored to the needs of rural communities. IAHS Medical Journal Vol 7(1), June 2024; 35-39